Penerapan Model Pembelajaran Think Pair Share Berbantuan Media Quizizz untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SD - Shelly Devi Yanti; Fachrurazi Fachrurazi; Novianti Novianti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Mathematical problem-solving ability is an important skill that students need to have to solve various problems logically and systematically. However, the mathematical problem-solving ability of fourth-grade students on plane geometry material is still relatively low. The purpose of this study is to improve students' mathematical problem-solving ability through the application of the Think Pair Share (TPS) learning model assisted by Quizizz. This study uses Classroom Action Research (CAR) which is implemented in two cycles through the stages of planning, implementation, observation, and reflection. The subjects of this study were 22 fourth-grade students at one of the Public Elementary Schools in Central Aceh Regency. Data collection techniques were carried out through tests to measure students' abilities on plane geometry material, as well as observation and interviews to obtain information about the learning process. The results of the study showed that the application of the Think Pair Share (TPS) model assisted by Quizizz was able to improve students' abilities in solving mathematical problems. Classical learning completeness increased from 31.81% in cycle I to 86.36% in cycle II. Teacher activity showed a percentage of 78.32% in cycle I and increased to 88.32% in cycle II. Meanwhile, student activity showed a percentage of 76.10% in cycle I and increased to 86.10% in cycle II. The research findings indicate that the implementation of the TPS model assisted by Quizizz is effective in improving the mathematical problem-solving skills of fourth-grade elementary school students on plane geometry.